PENENTUAN STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA USAHA KULINER DENGAN PENDEKATAN ANALYTICAL NETWORK PROCESS - Muhammad Israr Munggaran; Pitri Yandri (STIE DWI SAKTI BATURAJA, 2022)
The marketing strategy relates to making decisions about information about the company's products. Culinary business entities also really need to implement marketing strategies. This study aims to determine the best marketing strategy for a culinary business. We observed Warung Nasi Tutug Oncom; a culinary SMEs business in Pamulang, Tangerang Selatan Municipality. The sampling technique in this study used the purposive sampling technique, with a total of 5 respondents. The analysis technique uses analytical network process (ANP) techniques. ANP is one of the decision-making analysis techniques based on pairwise comparisons with specific criteria. The results of our research information that the most robust alternative is to carry out promotional and advertising activities to attract potential customers and expand the marketing area. This information can be essential for business actors in formulating marketing strategies.